2017
DOI: 10.3390/ijerph14060604
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Eye Injuries: A Relevant Health Problem. Main Epidemiological Data from a Highly-Industrialized Area of Northern Italy

Abstract: The province of Modena is one of the most industrialized areas of Northern Italy. The medical records of the Ophthalmological Emergency Department (OED) of Modena University Hospital were studied: there were 13,470 OED accesses in 2014 and in 754 cases that an occupational eye injury occurred. The frequency of work-related eye injuries (3‰) was lower compared to other published studies, but the absolute number is still relevant, showing the need for more adequate prevention, especially in metal work, construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 24 publications
6
34
1
5
Order By: Relevance
“…In contrast, studies showed a higher risk of ocular manifestations for older workers. (8,11,17) In addition, the current study found that port workers who performed their work activities in daytime shifts showed more ocular manifestations, with a 75.3% rate. A study carried out in China corroborated this finding, indicating a high prevalence of occupational ocular manifestations between 4 pm and 6 pm.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, studies showed a higher risk of ocular manifestations for older workers. (8,11,17) In addition, the current study found that port workers who performed their work activities in daytime shifts showed more ocular manifestations, with a 75.3% rate. A study carried out in China corroborated this finding, indicating a high prevalence of occupational ocular manifestations between 4 pm and 6 pm.…”
Section: Discussionsupporting
confidence: 52%
“…They resulted from foreign bodies; chemical agents, such as acids, alkaline, and detergents; and physical agents, such as acute exposure to optical radiation. (8) Ocular manifestations may be related to the failure to wear ocular protective devices. A study with the aim to assess awareness on ocular health hazards, related to work and use of personal protective equipment (PPE), showed an absence of these devices, high prices for personal acquisition or by the employer and, as for the few who wore the equipment, use was irregular due to discomfort, maladaptation, and vision impairment by haziness.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we decided to merge data from Agriculture and Industry & Services sectors, and to create a summarizing variable of the total number of skin cancers reported to INAIL for workers occupationally exposed to sUVR radiation and to other UVR sources. This seems legitimate, as there are no epidemiological data consistently showing an increasing in skin cancer risk for welders, which may be related to better skin cover in welders by, e. g. clothing and total face masks to avoid painful skin burns and other occupational eye injuries and diseases, including UV‐induced photokeratoconjunctivitis and photochemical cataract …”
Section: Discussionmentioning
confidence: 99%
“…6,9,39 Accordingly, we decided to merge data from Agriculture and Industry & Services sectors, and to create a summarizing variable of the total number of skin cancers reported to INAIL for workers occupationally exposed to sUVR radiation and to other UVR sources. This seems legitimate, as there are no epidemiological data consistently showing an increasing in skin cancer risk for welders, which may be related to better skin cover in welders by, e. g. clothing and total face masks to avoid painful skin burns and other occupational eye injuries 40 and diseases, including UV-induced photokeratoconjunctivitis and photochemical cataract. 6,41 Another possible limit of studying the expected number of occupational skin cancers in sUVR-exposed workers is related to cancer registries: while data on malignant melanoma are largely available since several years, in Italy, as in other countries, data for NMSC vary significantly in quality and coverage of the territory, due to insufficient data harmonization and heterogeneity of methods.…”
Section: Cancer Registries 2018mentioning
confidence: 99%
“…One deep gap that remains, even with these strategies, is in protecting/supporting at‐risk populations, such as immigrants and foreigners. These individuals present to emergency departments in a disproportionate amount and are typically less likely to wear eye protection than others . Court et al identify this risk factor in New Zealand, and anecdotally, similar trends appear in the United States as well.…”
mentioning
confidence: 99%